A Rare Case of Lateral Femoral Condyle Osteonecrosis of Knee in a Young Patient Treated with Robotic Total Knee Replacement: A Case Report - K T Rajashekhar; Kartik Mangsuli; Adarsh Krishna K Bhat (Journal of Orthopaedic Case Reports)
Introduction: Femoral condyle osteonecrosis of the knee leading to osteoarthritis is a rare entity, which is noticed more commonly in elderly women. Usually, the medial condyle is involved; lateral condyle involvement is extremely rare. Cases like these with occurrence in young individuals are even more rare and need thorough pre-operative evaluation, patient counseling, and intraoperative correlation for proper line of management. Based on the size and stage of the lesion, treatment options vary from medical management to biological therapies to arthroplasty in advanced cases. Case Report: A 17-year-old male with a body mass index of 29.6 presented to our outpatient clinic with complaints of pain over the left knee, difficulty in walking, squatting, and sitting cross-legged. He was examined clinically, radiologically, and intraoperatively based on the findings and was diagnosed with osteonecrosis of the lateral femoral condyle femur extending into the trochlea with arthritic changes. After detailed discussion and counseling with the patient and relatives, keeping in mind the patient’s demand and expectations, he underwent robotic-assisted total knee arthroplasty (TKA). Discussion: Knee osteonecrosis is a debilitating, progressive degenerative disease characterized by subchondral bone ischemia. It can lead to localized necrosis, tissue death, and progressive joint destruction. For this reason, it is essential to diagnose and treat this disease early to avoid subchondral collapse, chondral damage, and end-stage osteoarthritis, where the only management option is TKA. Conclusion: Osteonecrosis of the knee in young patients, particularly when there is extensive articular involvement and associated osteoarthritic changes, is quite challenging to treat. Although joint preservation is typically preferred in younger individuals, TKA may be the only viable option in advanced stages to restore function and quality of life. Robotic-assisted TKA allows for precise implant positioning and optimal alignment and thus enhances the functional outcome. Individualized treatment planning, thorough pre-operative evaluation, and comprehensive patient counseling are essential to achieving successful outcomes in such rare and complex cases.